Estimation of Generalized Impact Fraction and Population Attributable Fraction of Hypertension Based on JNC-IV and 2017 ACC/AHA Guidelines for Cardiovascular Diseases Using Parametric G-Formula: Tehran Lipid and Glucose Study (TLGS) - Saatchi M; Mansournia MA; Khalili D; Daroudi R; Yazdani K (Dove Medical Press, 2020)
Mohammad Saatchi,1 Mohammad Ali Mansournia,1 Davood Khalili,2 Rajabali Daroudi,3 Kamran Yazdani1 1Department of Epidemiology and Biostatistics, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran; 2Prevention of Metabolic Disorders Research Center, Research Institute for Endocrine Sciences, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 3Department of Health Management and Economics, School of Public Health, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Kamran YazdaniDepartment of Epidemiology and Biostatistics, School of Public Health, Tehran University of Medical Sciences, P.O. Box 644614155, Tehran, IranTel +98 912 297 9264Email kyazdani@tums.ac.irPurpose: An area of interest to health policymakers is the effect of interventions aimed at risk factors on decreasing the number of new cardiovascular disease (CVD) cases. The aim of this study was to estimate the generalized impact fraction (GIF) and population attributable fraction (PAF) of hypertension (HTN) for CVD in Tehran.Patients and Methods: In this population-based cohort study, 8071 participants aged ≥ 30 years were followed for a median of 16 years. A survival model was used to estimate the 10- and 18-year risk of CVD. JNC-IV and 2017 ACC/AHA guidelines were used to categorize blood pressure (BP). PAF and GIF were estimated in different scenarios using the parametric G-formula.Results: Of 7378 participants included in analyses, 22.7% and 52.3% were classified as hypertensive according to the JNC-IV and 2017 ACC/AHA guidelines, respectively. According to the 2017 ACC/AHA, the 10-year risk of CVD was 5.1% (4.3– 6.0%), 8.9% (6.7– 12.0%), and 7.1% (6.1– 8.4%) for normal BP, elevated BP, and stage 1 HTN, respectively, and 20.8% (18.8– 23.0%) for stage 2 of the 2017 ACC/AHA and JNC-IV. The PAF of stage 2 vs stage 1 and vs normal BP for CVD was 17.4% (11.5– 21.8%) and 20.4% (14.6– 26.4%), respectively. The GIF of 30% reduction in the prevalence of stage 2 HTN to stage 1 and to normal BP for CVD was 5.1% (3.4– 6.6%) and 6.1% (4.4– 8.0%), respectively. Based on JNC-IV, the PAF and GIF of 30% for CVD were 17.8% (12.7– 22.9%) and 5.4% (4.0– 6.9%), respectively.Conclusion: By reducing the prevalence of HTN by 30%, a remarkable number of new CVD cases would be prevented. In an Iranian population, the comparison of HTN cases with normal BP showed no association between stage 1 HTN and CVD, whereas elevated BP was a significant risk factor for the incidence of CVD.Keywords: generalized impact fraction, GIF, population attributable fraction, PAF, hypertension, cardiovascular diseases, 2017 ACC/AHA guidelines, parametric G-formula